Statistics of geomagnetic storms: Global simulations perspective - Pulkkinen, Tuija I.; Brenner, Austin; Al Shidi, Qusai; Toth, Gabor (Frontiers in Astronomy and Space Sciences, 2022)
We present results of 131 geomagnetic storm simulations using the University of Michigan Space Weather Modeling Framework Geospace configuration. We compare the geomagnetic indices derived from the simulation with those observed, and use 2D cuts in the noon-midnight planes to compare the magnetopause locations with empirical models. We identify the location of the current sheet center and look at the plasma parameters to deduce tail dynamics. We show that the simulation produces geomagnetic index distributions similar to those observed, and that their relationship to the solar wind driver is similar to that observed. While the magnitudes of the Dst and polar cap potentials are close to those observed, the simulated AL index is consistently underestimated. Analysis of the magnetopause position reveals that the subsolar position agrees well with an empirical model, but that the tail flaring in the simulation is much smaller than that in the empirical model. The magnetotail and ring currents are closely correlated with the Dst index, and reveal a strong contribution of the tail current beyond 8 $R_E$ to the Dst index during the storm main phase.